Management of epilepsy in patients with Rett syndrome: perspectives and considerations - Krajnc N (Dove Medical Press, 2015)
Natalija Krajnc Department of Child, Adolescent and Developmental Neurology, University Children’s Hospital, Ljubljana, Slovenia Abstract: Rett syndrome (RTT) is a common neurodevelopmental disorder that appears in infancy with regression of acquired motor skills, loss of purposeful activity, hand stereotypies, loss of acquired spoken language, and seizures. Epilepsy affects the majority of patients in a specific clinical stage of the disease and is drug resistant in approximately one-third of cases. The association of epilepsy and even drug-resistant epilepsy has been reported in certain genotypes of the methyl-CpG-binding protein 2 mutation, which is present in a majority of patients with classical RTT. The evolution of electroencephalographic abnormalities accompanying the clinical development of the syndrome is well described, but much less is known about the seizure semiology and the effectiveness of specific antiepileptic drugs. The aim of this review is to present the clinical and electrophysiological aspects of epilepsy in RTT and the current treatment approach. Keywords: Rett syndrome, epilepsy, treatment